2023
DOI: 10.1146/annurev-bioeng-092222-030857
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a Biological Variable in Tissue Engineering and Regenerative Medicine

Abstract: Although sex differences have been noted in cellular function and behavior, therapy efficacy, and disease incidence and outcomes, the adoption of sex as a biological variable in tissue engineering and regenerative medicine remains limited. Furthering the development of personalized, precision medicine requires considering biological sex at the bench and in the clinic. This review provides the basis for considering biological sex when designing tissue-engineered constructs and regenerative therapies by contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…However, these perspectives have been scarcely adopted by the biomedical engineering community. A survey (2017-2022) found that only 53-65% of engineered tissues considered sex and gender aspects [60]. Worse results are obtained when the community of biomaterials is considered, because only ∼4% of studies reported the cell sex, and none included it as a variable of interest [60].…”
Section: Are Natural and Synthetic And Biomaterials Sex-and Gender-su...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these perspectives have been scarcely adopted by the biomedical engineering community. A survey (2017-2022) found that only 53-65% of engineered tissues considered sex and gender aspects [60]. Worse results are obtained when the community of biomaterials is considered, because only ∼4% of studies reported the cell sex, and none included it as a variable of interest [60].…”
Section: Are Natural and Synthetic And Biomaterials Sex-and Gender-su...mentioning
confidence: 99%
“…For example, according to Lock and coworkers [64], the possibility of having female and male engineered myocardial tissues could help to elevate our knowledge on the effect of exogenous exposure to sexual hormones, and this could also improve myocardial health in transgender populations. Sex differences are not limited to cells but also involve micro-environments [60]. Indeed, physical signals (for example, size, shape, porosity, dimensionality) coming from the extracellular matrix are sex-dependent and may be affected by sex hormone stimulation [60].…”
Section: Are Natural and Synthetic And Biomaterials Sex-and Gender-su...mentioning
confidence: 99%
See 1 more Smart Citation
“…While sex was largely ignored in biomaterials research until recently, [ 267,268 ] some studies have demonstrated sex‐specific differences in host‐biomaterial interactions. For example, females have higher levels of myofibroblast activation and less calcification in aortic valves than males.…”
Section: Impact Of Other Biological Factors On Aging and Biomaterials...mentioning
confidence: 99%